'UF-404' – a New University of Florida Caladium Variety for Use in the Container and the Landscape - Zhanao Deng (EDIS)
ENH-1106, a 6-page illustrated fact sheet by Zhanao Deng, describes this red, lance-leafed caladium variety with a unique coloration pattern — its origin, tuber production, container forcing, landscape performance, chilling resistance and availability. Includes references. Published by the UF Department of Environmental Horticulture, November 2008.